Blind Painful Eye Revealing Spontaneously Regressed Retinoblastoma in Young Patient - Hadijah Hadijah; Halimah Pagarra; Suliati P. Amir; Andi Pratiwi (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Purpose: Spontaneous regression is a rare but well-known feature of retinoblastoma, which is predicted in approximately 2 of every 100 cases. Unilateral, unifocal spontaneous regression of retinoblastoma is infrequent; bilateral multifocal spontaneous regression of retinoblastoma is even more extraordinary. In many of the previously reported cases, the eye (or eyes) containing the spontaneously regressed tumor has been phthisical and blind. Herein, we describe the case of a young woman with unilateral, spontaneously regressed retinoblastoma (RB), with inflamed, blind, and phthisis in the left eye as an uncommon presentation of spontaneously regressed retinoblastoma Methods: This is a case report: An 18-year-old woman came to the outpatient clinic with a chief complaint of pain in the left eye since 1 month prior and a history of dysfunctional “cat’s” eye since childhood. Results: Exotropia and atrophy bulbi was noticed in the left eye. Anterior segment examination revealed signs of inflammation including conjunctival hyperemia, shallow anterior chamber, rubeosis iridis, and posterior synechia with white “chalky” mass suggestive calcification. B-scan ultrasonography showed a point like lesion and solitary solid intraocular mass with calcification in vitreus. Orbital computed tomography scan (CT-Scan) showed atrophy of the left eye with intraocular calcification without optic nerve and extraocular muscle involvement. Enucleation and histopathology examination were done and revealed undifferentiated retinoblastoma beyond the sign of metastasis in other parts of the eye. Conclusion: Blind painful eye may present as the main feature of spontaneously regressed retinoblastoma that possibly caused by an inflammatory reaction.